Penerapan Program Sadar Pendidikan Anak sebagai Upaya Meningkatkan Motivasi dan Disiplin Belajar - Nur Amalia Hildaini; M. Subdi; Edi Saputra; Meliya Meliya; Desma Ayu Artika; Dewi Molida; Muhammad Syahrul Hadi; Muhammad Hanapi; Serly Sofiana; Siti Khaerunnisa'; Sri Rodiatul Amini (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2026)
This community service activity aims to increase the learning motivation of school-age children and to increase parents' awareness of education through a child education awareness program implemented in Keroak Hamlet, Lenek Daya Village, Lenek District. This program uses a Participatory Action Research (PAR) approach by involving children, parents, and the community. The learning method applied is active learning with interesting learning media, carried out in 20 meetings with 30 children participating. The results of the activity showed an increase in learning motivation, including a 30% increase in school attendance, a 40% increase in reading habits at home, a 35% increase in homework activity, a 45% increase in reviewing lessons at home, a 40% increase in independent learning, a 45% increase in parental guidance, and a 45% increase in dedicated study time at home. These results indicate that the program not only improved children's motivation and discipline in learning but also encouraged parental involvement. It is hoped that this program can become a model for sustainable community service in rural areas.